Unpacking Argumentative Fallacies in Indonesia's 2024 Presidential Debates: A Cognitive-Pragmatic Analysis - Setyaningsih, Yuliana; Rahardi, R Kunjana; Rahmat, Wahyudi (Jurnal Gramatika, 2025)
This study examines the presence of argumentative inaccuracies in the 2023–2024 Indonesian presidential and vice-presidential debates through the lens of cognitive linguistics and contextual pragmatics. Using a qualitative descriptive approach, data were drawn from transcripts of five debate rounds and analyzed using Toulmin's model of fallacies combined with situational context theory. The research identifies five dominant fallacies: evading the issue, argument from ignorance, appeal to authority, ad hominem attacks, and hasty generalizations. Each fallacy is interpreted within its political and situational context—revealing how historical references, ethical deflections, appeals to seniority, lack of mastery, and satire are strategically employed. The findings offer insight into how these inaccuracies diminish the integrity of public political discourse and obscure substantive discussion of policies. Furthermore, the study underscores the critical role of context in shaping the interpretation and reception of political arguments. It contributes to the growing body of work on cognitive-pragmatic approaches in political linguistics, and emphasizes the need for educational efforts to cultivate critical thinking and argumentative literacy among citizens and students alike. This research also suggests practical implications for debate organizers, moderators, and media analysts—calling for clearer standards to reduce manipulative rhetoric in public forums. Future studies are encouraged to apply computational methods to expand this work or examine comparative debate formats across cultures.